2018
DOI: 10.1080/1343943x.2018.1439757
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variations in the plasticity of nodal root penetration through the hardpan during soil moisture fluctuations among four rice varieties

Abstract: Yamauchi (2018) Genotypic variations in the plasticity of nodal root penetration through the hardpan during soil moisture fluctuations among four rice varieties,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…Previous studies have shown experimental evidences of genotypic variations in root plasticity expressed in response to heterogeneous soil environments for the adaptation of rice plants (Bañoc et al, 2000a;Siopongco et al, 2008;Kano-Nakata et al, 2013;2017;Kameoka et al, 2015;Menge et al, 2016;Niones et al, 2012;Nguyen et al, 2018;Owusu-Nketia et al, 2018;Suralta et al, 2010Suralta et al, , 2016Suralta et al, , 2018Tran et al, 2014). In this study, the CSSLs showed no significant differences in root system development with the recurrent parent under CWL in both experiments.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Previous studies have shown experimental evidences of genotypic variations in root plasticity expressed in response to heterogeneous soil environments for the adaptation of rice plants (Bañoc et al, 2000a;Siopongco et al, 2008;Kano-Nakata et al, 2013;2017;Kameoka et al, 2015;Menge et al, 2016;Niones et al, 2012;Nguyen et al, 2018;Owusu-Nketia et al, 2018;Suralta et al, 2010Suralta et al, , 2016Suralta et al, , 2018Tran et al, 2014). In this study, the CSSLs showed no significant differences in root system development with the recurrent parent under CWL in both experiments.…”
Section: Discussionmentioning
confidence: 50%
“…The significant increase in shoot dry matter production of CSSL64, CSSL72 and CSSL79 under SMF conditions as compared with CWL in both experiments in this study contributed to their higher grain yields than KDML105 (Tables 1 and 2). This can be attributed to the increased production of tillers (Kanjoo et al, 2012) as well as water uptake and stomatal conductance (Kano-Nakata et al, 2013;Nguyen et al, 2018;Suralta et al, 2015;Tran et al, 2014). The significant and positive relationships between stomatal conductance and shoot dry matter ( Figure 5), under RFL condition in the field and that of total water uptake and shoot dry matter production (Figure 7(b)) under SMF in pot experiment indicate that water uptake and stomatal conductance enhanced dry matter production and consequently the grain yield of CSSL64, CSSL72 and CSSL79, which was significantly higher than that of KDML105.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…YTH183 can change its root cone angle to both wide and narrow according to the position of the water supply (Table 2 and Figure 2). Plasticity of the root system development in response to SMF has been studied in terms of root elongation and branching in rice (Kano-Nakata et al, 2013;Nguyen et al, 2018;Niones, Inukai, Suralta & Yamauchi, 2015;Owusu-Nketia et al, 2018;Suralta, Inukai & Yamauchi, 2010;Suralta et al, 2018bSuralta et al, , 2018a. Our study noted that plasticity of root growth angle was also exhibited under different soil water distribution in SMF, while most of the studies are focused on natural phenotypic variability of root growth angle (Bettembourg et al, 2017;Kato, Abe, Kamoshita & Yamagishi, 2006;Uga et al, 2015).…”
Section: Genotypic Variations In Plasticity Of Rsamentioning
confidence: 59%
“…, respectively. Measurement SMC were measured using Time Domain Reflectometry (TDR; Tektronix Inc., Wilsonville, OR, USA) based on the previous works (Kameoka et al, 2015;Nguyen et al, 2018;Suralta et al, 2018a). Two stainless steel rods (15 cm in length and 3 cm apart) were equally inserted into the side wall of the root box at 6.5 cm (upper), 19.5 cm (middle) and 32.5 cm (lower) from the top of the soil surface, allowing 3 cm protruding above the soil surface ( Figure S1a).…”
Section: Experimental Design and Treatmentsmentioning
confidence: 99%